How Cultural Goods Called K-Pop is Accepted in Asian Market – An International Joint Venture Approach - Saraswati, Alifia; Abdillah, Yusri; Damayanti, Cacik Rut (Profit: Jurnal Adminsitrasi Bisnis, 2023)
Nowadays, the cultural goods called K-Pop has spread around the world. Exportation of cultural goods is happening because of globalization that blurred the barrier of any state. The entry mode of the cultural goods exportation is considered easier than other exported goods since mostly people see that the usage of social media will result in making the cultural goods as something’s to be consumed with no meaningful modification. However, to give an absolute position in the target market, the focal company should have any information and knowledge about the local market. This knowledge and information are only be fulfilled by the local market company. This leads to the creation of the joint venture between the focal company and the local company. This research is explaining how the creation of joint venture between them is needed for the cultural goods exportation by using qualitative approach with case study method of SM Entertainment. This research is indicating that the entry mode toward target market in joint venture forms could also helping the exportation of cultural goods.